2003
DOI: 10.1242/jeb.00159
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar-type proton pump in the basolateral plasma membrane energizes ion uptake in branchial mitochondria-rich cells of killifishFundulus heteroclitus, adapted to a low ion environment

Abstract: SUMMARYWe examined the involvement of mitochondria-rich (MR) cells in ion uptake through gill epithelia in freshwater-adapted killifish Fundulus heteroclitus, by morphological observation of MR cells and molecular identification of the vacuolar-type proton pump (V-ATPase). MR cell morphology was compared in fish acclimated to defined freshwaters with different NaCl concentrations: low (0.1 mmol l-1)-, mid (1 mmol l-1)-and high (10 mmol l-1)-NaCl environments. MR cells, mostly located on the afferent-vascular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 48 publications
(32 reference statements)
2
88
3
Order By: Relevance
“…For example, the rates of Cl − uptake in larval (Bayaa et al, 2009) and adult zebrafish (Boisen et al, 2003), catfish (Goss et al, 1992) and rainbow trout (reviewed in Goss et al, 1994) have been reported as 200-700 μmol kg −1 h −1 , and are therefore comparable to the rates of HCO 3 − secretion (and thus Cl − uptake) in post-fed dogfish sharks. Additionally, basolateral VHA has been reported in gill ionocytes from freshwater stingray (Piermarini and Evans, 2001;Piermarini et al, 2002), bull shark (Reilly et al, 2011), killifish (Katoh et al, 2003) and rainbow trout (Tresguerres et al, 2006a), as well as in skin ionocytes from medaka embryos (Lin et al, 2012). An early study found evidence for Cl − /HCO 3 − exchange in the osmoconforming hagfish, and proposed that the driving force for the evolution of ion uptake in freshwater fish was A/B regulation (Evans, 1984).…”
Section: List Of Abbreviationsmentioning
confidence: 95%
“…For example, the rates of Cl − uptake in larval (Bayaa et al, 2009) and adult zebrafish (Boisen et al, 2003), catfish (Goss et al, 1992) and rainbow trout (reviewed in Goss et al, 1994) have been reported as 200-700 μmol kg −1 h −1 , and are therefore comparable to the rates of HCO 3 − secretion (and thus Cl − uptake) in post-fed dogfish sharks. Additionally, basolateral VHA has been reported in gill ionocytes from freshwater stingray (Piermarini and Evans, 2001;Piermarini et al, 2002), bull shark (Reilly et al, 2011), killifish (Katoh et al, 2003) and rainbow trout (Tresguerres et al, 2006a), as well as in skin ionocytes from medaka embryos (Lin et al, 2012). An early study found evidence for Cl − /HCO 3 − exchange in the osmoconforming hagfish, and proposed that the driving force for the evolution of ion uptake in freshwater fish was A/B regulation (Evans, 1984).…”
Section: List Of Abbreviationsmentioning
confidence: 95%
“…In tilapia, type-II and type-III MR cells are analogous to zebrafish NCC cells and HR cells, respectively. However, localization of H + -ATPase (with an anti-bovine adrenal medulla V-ATPase subunit A antibody) in tilapia embryonic skin was found to be confined to the apical membrane of pavement cells in a previous study (Hiroi et al, 1998), and this needs to be confirmed because different results were obtained using an antikillifish V-ATPase A subunit antibody (Katoh et al, 2003) (T. Kaneko and J. Hiroi, personal communication).…”
Section: Comparison Of Ionocytes Between Speciesmentioning
confidence: 95%
“…An ORF of 1,854 bp encoded a protein of 617 amino acids with a molecular mass calculated to be 68,168 Da. The bullfrog A-subunit showed the highest amino acid sequence similarity to the Xenopus laevis V-ATPase A-subunit (94%; AAH44025), followed by a high similarity to the rat (88%; XP-340988), mouse (88%; Laitala- Leinonen et al, 1996), human (88%; van Hille et al 1993), pig (87%; Sander et al 1992), and killifish A-subunits (87%; Katoh et al, 2003). Fig.…”
Section: Cloning Of A-and E-subunits Of V-atpasementioning
confidence: 99%